Classification of Cancers Diseases using Multivariate Analysis - Asia Hammood Hussein, Nabaa Naeem Mahdi, Haifa Taha Abd (Mathematical Statistician and Engineering Applications, 2022)
Cancer is a serious disease in Iraq due to the pollution of the environment as a result of the wars that Iraq fought. It turns out that there is no interest in studying cancer tumors as the mother of the disease, while we find that there is little interest in studying the causes of environmental pollution. Due to the importance of the topic, some types of cancerous diseases spread in each Iraqi governorate were studied through an analytical study using hierarchical cluster analysis methods. Data were collected on some cancerous diseases, including 901 cases infection with one of the cancerous tumors, and from the results of the analysis of hierarchical methods (The averages method between the groups, Single Linkage , The Complete Linkage , Average Linkage , Centroid Linkage, Midean linkage and the Ward method), which were similar in terms of convergence between the provinces for the similarity of the infection conditions with the difference in the numerical amount of coalescence only. It was found that the provinces of Babil, DhiQarudiala, and Najaf were close in terms of tumor incidence with the province of Erbil, while the province of Anbar converged with the province of Salah al-Din As for the governorates of Muthanna and Dohuk, Karbala, Wasit, Kirkuk, Sulaymaniyah, Maysan and Diwaniyah, they were associated with each other and contracted with the previous groups, then they contracted with the Nineveh Governorate and Basra. As for the governorate of Baghdad, we find it coalescing in the last stage with all the governorates.